1997
DOI: 10.1046/j.1365-2265.1997.d01-1737.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of transient hypothyroidism after iodine‐131 treatment in hyperthyroid patients with Graves' disease: prevalence, mechanism and prognosis

Abstract: These results indicate that (1) more than half the patients who developed hypothyroidism within 6 months after 131I treatment for Graves' disease recovered spontaneously, (2) TSAb activity might play some role in the recovery of transient hypothyroidism, and (3) the development of transient hypothyroidism may influence long-term thyroid function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 10 publications
2
32
1
4
Order By: Relevance
“…Early hypothyroidism seems related to the organ dose, whereas late hypothyroidism is probably related to an autoimmune process of GD (12,13). Similarly the numbers of patients with positive rTSHAb were not different among the three groups in our study, although some previous results suggest that rTSHAb activity may cause a recovery of cell function following irradiation and is associated with a relative resistance to radioiodine therapy (14). A plausible explanation may be that we did not have the opportunity to determine the amount of cAMP produced by rTSHAb on cultured cells and therefore to determine if these antibodies were stimulating or blocking.…”
Section: Discussioncontrasting
confidence: 43%
“…Early hypothyroidism seems related to the organ dose, whereas late hypothyroidism is probably related to an autoimmune process of GD (12,13). Similarly the numbers of patients with positive rTSHAb were not different among the three groups in our study, although some previous results suggest that rTSHAb activity may cause a recovery of cell function following irradiation and is associated with a relative resistance to radioiodine therapy (14). A plausible explanation may be that we did not have the opportunity to determine the amount of cAMP produced by rTSHAb on cultured cells and therefore to determine if these antibodies were stimulating or blocking.…”
Section: Discussioncontrasting
confidence: 43%
“…O tratamento com 131 I apresenta como principal efeito colateral uma alta incidência de hipotireoidismo permanente, cuja freqüência no primeiro ano de tratamento varia de acordo com a dose de 131 I administrada (64), enquanto que a incidência posterior (3% ao ano) depende de fatores imunológicos (65), da associação ou não com drogas antitireoidianas (66), tamanho do bócio (67), radiosensibilidade individual, homogeneidade da distribuição de iodo na glândula tireóide e duração do seguimento dos pacientes tratados (68). Hipotireoidismo transitório pode ocorrer no período de 2 a 5 meses após o uso do radioisótopo (9-58% dos casos) (69).…”
Section: Iodo Radioativo Iodo Radioativounclassified
“…Treatment with lithium prevented serum free T4 increase after methimazole withdrawal and RAI therapy. At last, studies have shown that RAI is safe and except of transient or permanent iatrogenic hypothyroidism no significants outcomes have been reported (5). In a follow up study for 20 years, Ron and cols.…”
Section: Discussionmentioning
confidence: 97%